2013
DOI: 10.1111/are.12334
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in lipid metabolism and stress tolerance of juvenile giant grouper,Epinephelus lanceolatus(Bloch), fed supplemental choline

Abstract: Six fish meal basal diets supplied with 0 (control), 0.25, 0.5, 1, 2.5 and 5 g kg À1 of choline chloride, resulting in choline levels of 2.57, 2.67, 2.94, 3.84, 4.99 and 7.71 g kg À1 , respectively, were fed to giant grouper, Epinephelus lanceolatus, for 56 and 30 days to evaluate the growth and lipid metabolism, and stress tolerance respectively. In the first trial, fish fed different levels of cholinecontaining diets for 56 days had no significant difference in weight gain, survival and feeding efficiency. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…However, there were no apparent indications of reduced performance as a result of choline dose nor LMS, for which no significant differences on growth nor macronutrient digestibilities were observed. The present observation of choline not affecting growth is in agreement with some previous studies on adult Atlantic salmon (72) , channel catfish (7) and giant grouper (73) . However, in our previous study with large Atlantic salmon (3) and in several other studies with juveniles from different species (5,10,13,(74)(75)(76)(77) , increased growth with choline supplementation has been observed.…”
Section: Dietary Choline Level Effects On Performancesupporting
confidence: 94%
“…However, there were no apparent indications of reduced performance as a result of choline dose nor LMS, for which no significant differences on growth nor macronutrient digestibilities were observed. The present observation of choline not affecting growth is in agreement with some previous studies on adult Atlantic salmon (72) , channel catfish (7) and giant grouper (73) . However, in our previous study with large Atlantic salmon (3) and in several other studies with juveniles from different species (5,10,13,(74)(75)(76)(77) , increased growth with choline supplementation has been observed.…”
Section: Dietary Choline Level Effects On Performancesupporting
confidence: 94%
“…Liver glycogen content in fish fed the CHO/L ratio of 1.25 or 1.88 was significantly higher than fish fed the CHO/L ratio of 0.13, 0. 4 [16] and lipid, respectively [17,18]. It was reported that fish larvae utilize dietary phospholipids more efficiently than neutral lipids [19] and have high requirements of phospholipids such as at least 9.5% for pikeperch larvae [20] and 6.95-8.51% for large yellow croaker larvae [21] so in this study, 10% of soy lecithin was supplemented to all experimental diets.…”
Section: Introductionmentioning
confidence: 92%
“…Giant grouper Epinephelus lanceolatus has been widely cultured in China in recent years due to its faster growth compared to other grouper species [16]. To date, available information on nutrition of Epinephelus lanceolatu is quite limited, with only one published study [16] evaluating effects of choline on lipid metabolism and stress tolerance of juvenile giant grouper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total lipids in the liver and plasma significantly decreased in S. ocellatus fed a choline-free diet [1]. In contrast, the hepatosomatic lipid concentration and hepatopancreatic index are higher in choline-deficient P. monodon [9] and Epinephelus lanceolatus [12]. The whole-body crude protein is also higher in P. monodon fed given 4000 and 7000 mg/kg dietary choline [2].…”
Section: Introductionmentioning
confidence: 93%